Pemanfaatan Google Sites dalam Pemasaran Digital UMKM KTH Permata - Timo, Fredirikus; Gelu, Leonard Peter; Klau, Anggelina Delviana (Journal of Research Applications in Community Service, 2026)
Micro, Small, and Medium Enterprises (MSMEs) of the Forest Farmer Group (KTH) Permata have traditionally marketed local products such as instant ginger herbal drink, instant turmeric herbal drink, instant temulawak, and forest honey using conventional methods, resulting in limited market reach and suboptimal income. Marketing through social media platforms such as Facebook and WhatsApp has not been fully optimized due to limited understanding of digital marketing management, particularly the use of websites as official marketing media. This community service activity aimed to provide training and mentoring for MSMEs KTH Permata members on the utilization of Google Sites as a digital marketing medium. The methods included observation to identify existing conditions and problems, discussions with partners to formulate solutions, documentation, implementation of Google Sites management training, and evaluation through questionnaires to measure improvements in participants’ skills. The results showed that the training and mentoring activities improved participants’ understanding and skills, with 80% of members successfully creating and publishing Google Sites websites independently, while 70% were able to manage and update product content on a sustainable basis. The outputs of this activity included the availability of an official marketing website for MSMEs KTH Permata featuring business profiles, product catalogs, and contact information, which contributed to expanding market reach and increasing product visibility. In conclusion, limited knowledge and skills were the main barriers to digital marketing adoption; however, the training and mentoring proved effective in strengthening MSME capacity to utilize Google Sites as a digital marketing tool.